The Role of Culture in Language and Communication - Prof. David Johnson; Elena Sánchez (CINEFORUM, 2023)
Culture, in its myriad forms, serves as an indelible tapestry woven into the very fabric of human communication. offers a succinct overview of the profound and intricate role that culture playsin shaping language and communication. It recognizes that beyond being a mere vehicle of expression, language is a reflection of the rich tapestry of values, beliefs, customs, and shared experiences that define a community’s cultural identity. The relationship between culture and language is a dynamic interplay that extends beyond the boundaries of linguistic systems. Culture shapes the very way we perceive the world, influencing the words we choose, the meanings we attach to them, and the nuances we convey through tone, gesture, and context. It is the wellspring from which language draws its depth and richness.